The Amazonian Goblin Spiders of the New Genus Gradunguloonops (Araneae: Oonopidae) - Grismado, Cristian J.; Izquierdo, Matías A.; Márquez, María E. González; Ramírez, Martín J. (Zootaxa, 2015)
A new genus of soft-bodied oonopids, Gradunguloonops, is established for a group of goblin spiders found in the Amazonian rainforests of northern South America. Members of this genus differ from other oonopids in that the proclaw of tarsi I and II is notably larger than the corresponding retroclaw, a putative synapomorphy of the group. Gradunguloonops comprises twelve species, all new and described in this contribution: G. mutum (type species) from Brazil and Peru, G. bonaldoi, G. amazonicus, G. urucu, G. pacanari, G. juruti from Brazil, G. erwini from Peru, G. orellana and G. nadineae from Ecuador, G. benavidesae and G. florezi from Colombia, and G. raptor from Venezuela. Two preliminary intrageneric groups are proposed on the basis of their female genital morphology: the bonaldoi group, to which are assigned the species with the anterior section comprising only a single anterior sclerite, and the mutum group, with a more complex, tripartite anterior section.